Evaluating the economic value of local culture and arts festival entrance fee to using contingent valuation method - Sungjin Yang; Seolwoo Park (Global Business & Finance Review (GBFR), 2024)
Purpose: Global cultural and arts festivals are often cited to enhance the image of a region and stimulate its economy. However, research and discussions regarding these global cultural and arts festivals have mainly focused on their outcomes and strategies for activation, with limited emphasis on evaluating the intrinsic value of the fes-tivals themselves, particularly their economic value. The aim of this study is to define global cultural and arts festivals and propose methods for estimating their economic value. Design/methodology/approach: This study employed the Contingent Valuation Method (CVM) to assess the eco-nomic value of cultural and arts festivals. A representative global cultural and arts festival was selected, and a double dichotomous choice contingent valuation method was utilized to propose a method for assessing willing-ness-to-pay (WTP) for cultural and arts festivals. Following a survey to investigate respondents' WTP and the value of 263 valid copies, data were analyzed using SPSS and STATA. Findings: In this study, we aimed to estimate the WTP per person for the admission fee of the Jeju International Wind Ensemble Festival (JIWEF) and demonstrate the versatility of this methodology through analysis using various data sources. Additionally, we estimated the economic value of the admission fee for the JIWEF, by multiplying the WTP per person for the admission fee by the average number of attendees. Research limitations/implications: Although there are limitations to generalization focusing on specific festivals, the research results suggest implications for foreign visitor arrivals and nurturing global consumers through global culture and arts festivals. Originality/value: So far, research related to culture and arts festivals has mainly focused on the festival's perform-ance or revitalization measures, and research on the evaluation of the value of the culture and arts festivals them-selves, especially their economic value, has not been actively conducted. This study is different in this regard.
Keywords: 650; Culture and arts festival; Jeju International Wind Ensemble Festival; Economic value; Contingent valuation method; Willingness to pay